The Home edit life : the no-guilt guide to owning what you want and organizing everything - Shearer, Clea, 1982-; Teplin, Joanna, 1979- (Clarkson Potter/Publishers, 2020)
"The New York Times bestselling authors, of The Home Edit, show you how to contain the chaos and organize every aspect of your life, including hobbies and activities, work and office spaces, luggage and travel, and so much more"--